Determination Of Hematological Parameters (Hemogram and Leukogram) In Blood Serum in Women with Generalized Periodontitis, Whose Pregnancy Is Complicated by Iron Deficiency Anemia - Sodiqova Shoira Amriddinovna; Mavlonov Shoxrux; Nasimov Amir; Nasrullaev Javlonbek (Academia One Publishing, 2024)
Pregnancy is a crucial phase in a woman's life, characterized by numerous physiological changes. Among these changes, alterations in hematological parameters are significant and can be influenced by various factors. Generalized periodontitis, a prevalent inflammatory condition of the gums, coupled with iron deficiency anemia, adds complexity to this delicate phase of gestation. This article aims to explore the correlation between hematological parameters, especially hemogram and leukogram, in pregnant women experiencing both generalized periodontitis and iron deficiency anemia
Keywords: hematological parameters; hemogram; leukogram